Developing inference-making through explicit instructions - Al Jahwari, Yahya Sulaiman; Sheikh Ahmad, Ismail (Impact Journals, 2022)
This part is related to a larger study exploring the implementation of inference-making strategies in reading comprehension lessons. This part of the study focused on the best way to develop inference-making when teaching reading comprehension. There is significant evidence that reading comprehension has long been a popular topic in educational contexts. The level of reading comprehension can be influenced by a variety of elements such as cognitive capacity, a lack of vocabulary, text complexity, reading techniques, and students' prior knowledge. As a result, readers must be able to use a variety of reading strategies in order to comprehend the reading texts, such as making connections, asking questions, inferring meaning, summarizing main ideas, and drawing conclusions. In this perspective, inference-making is regarded as the most important part of the reading process. It is the ability to deduce meaning from textual and contextual information. As a result, it has been proven that explicitly teaching children how to draw conclusions and make inferences can improve their understanding of what they're reading.